Effect of compound Musizin isolated from Rhamnus wightii Wight and Arn on the immature stages of filarial vector mosquito Culex quinquefasciatus Say (Diptera: Culicidae) and its non-target studies. (October 2018) - Raja, Tharsius Raja William; Ganesan, Pathalam; Gandhi, Munusamy Rajiv; Duraipandiyan, Veeramuthu; Paulraj, Michael Gabriel; Balakrishna, Kedike; Al-Dhabi, Naif Abdullah; Ignacimuthu, Savarimuthu
Abstract: The present study was aimed to check the activity of Rhamnus wightii Wight and Arn against Culex quinquefasciatus (Say). Eggs and larvae of Cx. quinquefasciatus were exposed to different concentrations (0.5, 1.0, 1.5 and 2.0 ppm) of R. wightii crude extracts prepared using DMSO. The active ethyl acetate extract was packed in column chromatography and eluted. Totally 10 fractions were obtained based on the TLC profile. Among these fractions, fraction 2 obtained from Hexane:Chloroform (1:1) presented promising larvicidal activity compared to the other fractions. This fraction was identified as Musizin. Musizin caused 70% larvicidal activity with LC50 and LC90 values of 1.62 and 4.51 ppm respectively at 24 h. The larvae exhibited restless movement and convulsion followed by death; in control the larvae presented normal movement. Musizin presented 83% ovicidal activity against Cx. quinquefasciatus eggs after 120 h post-treatment at 2 ppm. Musizin treated eggs were shrunken, and most of the eggs did not hatch. Musizin was tested for toxicity against non-target organism Poecilia reticulata, and no toxicity was found against this organism. Musizin treated larvae were subjected to histopathological studies, and the results revealed severe damage to the larval midgut cells; in control there was no damage in the midgut cells of larvae. The present study revealed that the isolated compound Musizin could be used as a natural pesticide to control vector mosquitoes. Highlights: Chemical insecticide are effective to the mosquitoesbut cause environmental and public health problems. Compounds from natural sources are toxic to the vector mosquito and beneficial to the environment. Musizin caused 70% larvicidal activity against third in star larvae of Cx. quinquefasciatus respectively at 24h. Eighty three percentage of ovicidal activity was recorded against Cx. quinquefasciatus eggs after 120h post-treatment at 2ppm. Histopathological study revealed Musizin treated larvae caused serious damage on the larval midgut cells.